2014
DOI: 10.1097/wnp.0000000000000108
|View full text |Cite
|
Sign up to set email alerts
|

Normal Values of Posterior Antebrachial Cutaneous Nerve Conduction Study Related to Age, Gender, Height, and Body Mass Index

Abstract: This study has established normal values for PABC nerve conduction studies. Furthermore, age and body mass index must be taken into account for making diagnostic conclusion in PABC nerve conduction studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
15
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 13 publications
7
15
2
Order By: Relevance
“…Regression analysis showed that there was not a significant adjusted effect of height on different SNAP parameters in multiple linear regression analysis by controlling the other assessed factors (i.e., age, gender, and other anthropometric measures). These were in accordance with Sajadi et al and in agreement with previous studies [6,14,28,29]. The SNAP CV is affected by the height of the subjects in the nerve conduction studies of the lower limbs [27].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Regression analysis showed that there was not a significant adjusted effect of height on different SNAP parameters in multiple linear regression analysis by controlling the other assessed factors (i.e., age, gender, and other anthropometric measures). These were in accordance with Sajadi et al and in agreement with previous studies [6,14,28,29]. The SNAP CV is affected by the height of the subjects in the nerve conduction studies of the lower limbs [27].…”
Section: Discussionsupporting
confidence: 93%
“…Regression analysis showed that there was not a significant adjusted effect of gender on different SNAP parameters in multiple linear regression analysis by controlling the other assessed factors (i.e., age and different anthropometric measures). These were in accordance with previous studies [4,6], as well as previous studies which assessed other nerves as ulnar palmar cutaneous nerve, medial antebrachial cutaneous nerve, and lateral antebrachial cutaneous nerve [14,19,20]. But, these were not in accordance with that reported in the literature [21][22][23][24].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…6 Using the same reference data in patients with different gender may result in errors in reporting and hence need to have separate refrence data for both sexes for clinical purpose. 7,8 The present study was therefore designed to gather reference data for healthy male and female students in Bathinda district, by doing nerve conduction study medical students of Adesh Institute of Medical Sciences and Research Bathinda, having no exposure to forceful or repetitive hand exertions, or segmental vibration. While some studies have excluded subjects with peripheral nerve disease, 9,10 but no study has specified the occupations of their subjects or excluded population with low exposure to known occupational Section: Physiology risk factors for carpal tunnel syndrome such as force, repetitiveness, and vibration.…”
Section: Introductionmentioning
confidence: 99%